-4(4b+2)+(17b-3)=0

Simple and best practice solution for -4(4b+2)+(17b-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(4b+2)+(17b-3)=0 equation:


Simplifying
-4(4b + 2) + (17b + -3) = 0

Reorder the terms:
-4(2 + 4b) + (17b + -3) = 0
(2 * -4 + 4b * -4) + (17b + -3) = 0
(-8 + -16b) + (17b + -3) = 0

Reorder the terms:
-8 + -16b + (-3 + 17b) = 0

Remove parenthesis around (-3 + 17b)
-8 + -16b + -3 + 17b = 0

Reorder the terms:
-8 + -3 + -16b + 17b = 0

Combine like terms: -8 + -3 = -11
-11 + -16b + 17b = 0

Combine like terms: -16b + 17b = 1b
-11 + 1b = 0

Solving
-11 + 1b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 1b = 0 + 11

Combine like terms: -11 + 11 = 0
0 + 1b = 0 + 11
1b = 0 + 11

Combine like terms: 0 + 11 = 11
1b = 11

Divide each side by '1'.
b = 11

Simplifying
b = 11

See similar equations:

| n/4-10=4 | | 4x^2+23x+15/4x+3 | | 2x^2-36=6 | | 3/7x^2/3x+5/21x^3-35x^2 | | 9+5r=-17-8 | | 5.7q-2.8-5.5q=-0.8q-3.1 | | 3(p+5)=19+p | | x^2+10x-113.09= | | n/12-3=5 | | 13x=3/4 | | x^2+13x-4=0 | | 5x^3-6x^2-35x+42=0 | | n/9-8=4 | | .285n-5=5 | | X+4X+(5X-14)=180 | | w/4-6w/8+9/2=w+6/8 | | 4/3b-1/b^2+2b | | x^2-3*x+k^2=4 | | X+4X+(5X-14X)=180 | | n+5=29 | | 4x-y=600 | | 7x+16x=161 | | 11x+2x^2=63 | | y=Ix-3I+2 | | 225x+100+144x=-2969 | | 12+5x=2(x-6) | | r/14=4 | | 13x+14=7x+14 | | 0=-16t+116t+101 | | 0=0.74b+1.26b-2b | | 12.8/8 | | 9x+8x-10x-5x+3x-23=15-8 |

Equations solver categories